Backlash : [compact disc, unabridged] / a thriller - Thor, Brad (Thor, Brad. Scot Harvath., 2019)
Far from home and surrounded by enemies in the wake of an unforgivable betrayal, Scot Harvath tests the limits of his training in an effort to escape and exact revenge.